2011
DOI: 10.5897/ajmr11.782
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility and toxins production of Staphylococcus aureus isolated from clinical samples from Benin

Abstract: A wide range of clinical samples were screened for identification of Staphylococcus aureus, their antibiotic sensitivity profile and the production of different leucotoxin and epidermolysins was evaluated. Out of 2,040 biological samples (collected from pus, urine, sperms, genital, catheter and blood of hospitalized and extra-hospital patients) screened, 123 pure cultures of S. aureus colonies were isolated. 48.78% of S. aureus were resistant to methicillin (MRSA), while 78% of them were isolated from extra-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
(38 reference statements)
3
14
0
1
Order By: Relevance
“…Out of the 206, MRSA were 99 (48%) and MSSA were 107 (51.9%) as shown in [12,13,14,15] In the present study, the prevalence of S. aureus isolates in OPD, IPD and ICU was 49.0%, 40.3% and 10.7% respectively. The prevalence of MRSA was 48.5% in OPD, 48.2% in IPD and 45.5% in ICU.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Out of the 206, MRSA were 99 (48%) and MSSA were 107 (51.9%) as shown in [12,13,14,15] In the present study, the prevalence of S. aureus isolates in OPD, IPD and ICU was 49.0%, 40.3% and 10.7% respectively. The prevalence of MRSA was 48.5% in OPD, 48.2% in IPD and 45.5% in ICU.…”
Section: Resultsmentioning
confidence: 81%
“…Our study showed 36.4% resistance towards Gentamicin which was similar to a study conducted in South East Nigeria in 2016 by Chijioke A Nsofor et al where Gentamicin resistance was 31.7%. [13] Two other similar studies conducted by Dhanalakshmi TA et al [20] and Sina H et al [12] showed 33.6% and 42.27% resistance respectively towards Gentamicin. On the other hand, in present study, the resistance pattern for Ciprofloxacin was found to be 40.3%.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations